2009
DOI: 10.1623/hysj.54.5.872
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of the model complexity required in runoff simulation at different time scales / Etude de la complexité de modélisation requise pour la simulation d'écoulement à différentes échelles temporelles

Abstract: The "optimal" model complexity is defined as the minimum watershed model structure required for realistic representation of runoff processes. This paper examines the effects of model complexity at different time scales, daily and hourly. Two watershed models with different levels of complexity were constructed and their capability to simulate runoff from a watershed was evaluated. Both models were tested on the same watershed using identical meteorological input, thereby assuring that any difference between mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(3 citation statements)
references
References 22 publications
0
3
0
Order By: Relevance
“…This is a continuous hydrological model and only need Pr, Tmax, and Tmin to simulate flow. As the UBCWM was designed from minimum meteorological parameters, it is very useful in the mountainous watershed, for example, Campbell River watershed where meteorological and flows data are often spare (Micovic & Quick, ). Because the hydrologic response of a mountainous watershed depends on elevation, UBCWM adapted the “area‐elevation band” concept.…”
Section: Methodsmentioning
confidence: 99%
“…This is a continuous hydrological model and only need Pr, Tmax, and Tmin to simulate flow. As the UBCWM was designed from minimum meteorological parameters, it is very useful in the mountainous watershed, for example, Campbell River watershed where meteorological and flows data are often spare (Micovic & Quick, ). Because the hydrologic response of a mountainous watershed depends on elevation, UBCWM adapted the “area‐elevation band” concept.…”
Section: Methodsmentioning
confidence: 99%
“…This high seasonal resolution, which is becoming widely used in hydroclimatological analyses (e.g., [13,19,28,29,78]), facilitates the study of seasonally transient physical hydrologic processes (such as the onset of the spring snowmelt freshet, or late-summer peak glacier meltwater production following exhaustion of the seasonal snowpack), which may last only a few weeks and can be easily obscured in monthly or seasonal averages or totals. It also expedites the identification of nonlinear effects which can similarly be lost to such temporal aggregation [13,34,53,62,66]. Previous work has empirically demonstrated that the specific data processing and analysis methods used here enable detection of statistically and physically significant hydrologic teleconnections that cannot be identified using more temporally coarse-grained datasets [19].…”
Section: Methodsmentioning
confidence: 99%
“…The argument about model structural error suggests that future modeling systems should be able to account for these uncertainties with different model structures. Micovic and Quick (2009) look at the complexity of model representation needed as the temporal resolution of the hydrologic model decreases. So as simulations move from long-term climate simulations at a daily time step to simulations for individual days with extreme flood events is there a need for more hydrologic model complexity?…”
Section: Review Of Existing Hydrologic Modelsmentioning
confidence: 99%